I have solved the first one. Hope this helps
Answer:
-3
Step-by-step explanation:
Simplifying
4(4m + -3) + -1(m + -5) = -52
Reorder the terms:
4(-3 + 4m) + -1(m + -5) = -52
(-3 * 4 + 4m * 4) + -1(m + -5) = -52
(-12 + 16m) + -1(m + -5) = -52
Reorder the terms:
-12 + 16m + -1(-5 + m) = -52
-12 + 16m + (-5 * -1 + m * -1) = -52
-12 + 16m + (5 + -1m) = -52
Reorder the terms:
-12 + 5 + 16m + -1m = -52
Combine like terms: -12 + 5 = -7
-7 + 16m + -1m = -52
Combine like terms: 16m + -1m = 15m
-7 + 15m = -52
Solving
-7 + 15m = -52
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '7' to each side of the equation.
-7 + 7 + 15m = -52 + 7
Combine like terms: -7 + 7 = 0
0 + 15m = -52 + 7
15m = -52 + 7
Combine like terms: -52 + 7 = -45
15m = -45
Divide each side by '15'.
m = -3
Simplifying
m = -3
Hope this helped :)
There are two ways you can do this. You can use the longer way:
15+16+17+18+19+20+21+22+23+24 = 195 (starting from the top row, which has 15 logs, up until the bottom row, which has 24 logs, on condition that each second row has one log more than the previous one)
You can also use the formula (where n is the number of rows)
x= (n(first term+last term))/2
x= (10(15+24))/2
x= (10*39)/2
x=390/2
x=195
Either way, there are 195 logs in the stack.
We need to cross multiply to solve it.
After we cross multiply we get
6x-1 = 3 x 5
6x-1 = 15
6x = 16
x = 16/6
x = 8/3
Hope that helps :D
It would be D , please tell me if I’m correct